Entrepreneurship Training of Culinary Business for Micro Small Medium Entrepreneurs in Bojong Soang, Bandung, Indonesia - Malinda, Maya; Margaretha, Yolla; Suwarno, Henky Lisan; Aliwinoto, Christine (RSF Conference Series: Business, Management and Social Sciences, 2022)
Business success is determined by many factors, one of which is determined by having the ability or entrepreneurial skills. By looking at government directives that are serious about developing Micro, Small and Medium Enterprises (MSMEs) to improve their entrepreneurial abilities and skills, research is in synergy with the university research roadmap, namely Enhancing competent, professional, and creative Human Resources so that they become entrepreneurs based on the creative economy. There needs to be efforts to improve entrepreneurial skills. The purpose of this research is to map the condition of MSME actors in Bojong Soang, Bandung, West Java, Indonesia, especially those who have culinary businesses. Support the government in terms of alleviating poverty problem through capacity building and skills among MSME entrepreneurs; Assist the government through appropriate training methods to improve Entrepreneurship Training for MSME entrepreneurs with special topic Business Canvas Model; combines expertise from various fields. The research method we use is quantitative research method with descriptive study case format. Collecting data in Bojong Soang, Bandung, West Java, Indonesia on 76 MSME culinary business. The Research founding after entrepreneurship training, give good result that in range 77% -97% MSME know or understand their Business Model. Women MSME have high formal education than man MSME. Mostly MSME need sales and marketing topic to make them business growth.